Calculate The Estimated Loading Time of Caustic Soda According on The Amount of Caustic Soda Loaded on MT AKRA 102 - Guntoro, Herlan; Yudhiyono; Parulian, Daniel (Meteor STIP Marunda, 2023)
Loading operations on chemical tankers require precise time estimation to ensure port efficiency and operational safety. This study aims to formulate and validate a mathematical model for calculating the Estimated Loading Time (ELT) of Caustic Soda (NaOH 50% solution) on MT AKRA 102, a chemical/oil product tanker with a Deadweight Tonnage (DWT) of 5,692 metric tons. The research employs a descriptive quantitative approach incorporating cargo density conversion (ρ ≈ 1.515 t/m³), shore pumping transfer rates, and standardized operational safety margins—comprising initial slow-rate loading, topping-off sequences, and inspection allowances. Three loading scenarios with pumping rates of 150, 250, and 350 MT/hour were simulated for a cargo quantity of 4,500 MT, yielding total estimated loading times of 33.00, 21.00, and 15.86 hours, respectively. Validation against actual field data demonstrated that the model achieves discrepancies within acceptable operational thresholds, confirming its reliability for pre-voyage loading time planning. The findings contribute practical tools for port clearance scheduling and chemical tanker operational efficiency.